Estimation and Mapping of Carbon Footprint in Transportation Sector (Case Study of Traffic Activities in East Karawang and West Karawang Sub-district) - Arsya, Zahira; Adzillah , Wilma Nurrul; Komarudin, Nurul Amri (Jurnal Agroekoteknologi Terapan, 2025)
The high carbon emissions from the transportation sector due to the growth of motor vehicles in East Karawang and West Karawang sub-districts prompted the need for carbon footprint estimation and mapping. This study aims to estimate and map the transportation sector's carbon footprint based on traffic activities in East Karawang and West Karawang subdistricts. Data was collected through a questionnaire survey to 100 respondents representing eight villages in each sub-district, supported by secondary data from relevant agencies. Information collected included vehicle type, type and amount of fuel used, and vehicle mileage. Emission calculations were conducted using the IPCC method by considering emission factors, net heating value (NCV), and fuel density. Results show that total emissions in East Karawang reached 121.03 tons of CO₂eq/year, highest in Warungbambu Village (28.93 tons), while West Karawang produced 126.08 tons of CO₂eq/year, highest in West Adiarsa (43.17 tons). The highest emissions generally come from the use of RON 90 fuel. Spatial analysis using QGIS shows that the distribution of emissions varies between villages grouped into eight categories. This research can provide a spatial picture that can be used by the government for policies related to reducing emissions in areas that are still high in emissions. Keywords: carbon footprint, CO2 emission, East Karawang, transportation, West Karawang, QGIS.